Study of Ecology and Biodiversity Learning Based on Project Based Learning-Science Technology Engineering Mathematics (PjBL-STEM) in Empowering Students' Critical Thinking - Hikmah Fatimah; Sri Yamtinah; Bramastia Bramastia (Jurnal Penelitian Pendidikan IPA, 2023)
The Project-Based Learning-Science Technology, Engineering Mathematics (PjBL-STEM) model is needed to empower students' critical thinking abilities and independence. PjBL-STEM implementation has been carried out in various fields of study and at various levels. A comprehensive study is needed to map the potential opportunities and limitations of implementing PjBL-STEM, including its influence on students' thinking skills. Therefore, this research aims to conduct a comprehensive literature review regarding implementing PjBL-STEM to improve students' critical thinking skills. In particular, this study is correlated with the potential implementation of PjBL-STEM in Ecology and biodiversity material. The literature review method was used in this research. The scientific articles selected in this study are those indexed on Google Scholar and published in 2010-2022. The keywords â€œPjBL-STEM and Critical Thinkingâ€ were used as the initial basis for selecting articles. After applying the criteria and article limitations, 90 articles were obtained for analysis. The results of this study show that the implementation of PjBL-STEM in empowering critical thinking is carried out at the elementary school to tertiary level. Apart from that, implementing PjBL-STEM is also done in general research, such as developing teacher competencies. The strengths, weaknesses, challenges, and obstacles that may occur when applying the PjBL-STEM model to ecology and biodiversity material in empowering students' critical thinking are discussed in this article